Analisis Semiotika Subordinasi Perempuan dalam Lirik Lagu Bernadya - Faiza Riani (Komuniti : Jurnal Komunikasi dan Teknologi Informasi, 2025)
Penelitian ini menganalisis subordinasi perempuan dalam tiga lirik lagu Bernadya (“Satu Bulan”, “Apa Mungkin”, dan “Kata Mereka Ini Berlebihan”) dengan pendekatan semiotika Roland Barthes untuk mengungkap lapisan makna denotatif, konotatif, dan mitos dalam lirik lagu sebagai budaya populer. Dalam Muted Group Theory, perempuan digambarkan sebagai kelompok terbungkam, terjebak dalam narasi ketimpangan kuasa dan gender yang tidak setara. Berbeda dengan penelitian terdahulu mengenai analisis gender dalam teks media yang sarat dengan pesan-pesan pemberdayaan perempuan, penelitian ini menemukan adanya romantisasi ketimpangan gender melalui subordinasi perempuan yang disebabkan oleh budaya patriarki. Dengan melihat musik sebagai medium untuk mencerminkan dan membentuk nilai-nilai sosial yang berlaku di masyarakat, internalized misogyny berpotensi terjadi dari Bernadya, penyanyi perempuan Indonesia, kepada audiensnya yang berjenis kelamin perempuan.   This study analyzes the subordination of women in three of Bernadya’s song lyrics (“Satu Bulan,” “Apa Mungkin,” and “Kata Mereka Ini Berlebihan”) using Roland Barthes’ semiotic approach to examine the layers of denotative, connotative, and mythical meanings within song lyrics as a form of popular culture. In Muted Group Theory, women are depicted as a silenced group, trapped in narratives of unequal power and gender imbalance. This research finds a romanticization of gender inequality through the subordination of women, rooted in patriarchal culture. The analysis shows that the process of denotative meaning evolves into connotative layers that generate myths about women as weak, doubtful, and emotionally dependent on men. These myths indirectly reinforce patriarchal values and portray women in subordinate positions. These findings also reinforce the Muted Group Theory, in which women struggle to express their perspectives freely within a male-dominated social structure. Additionally, this study identifies a tendency toward internalized misogyny within the lyrical narratives being analyzed.